mu SR study of organic systems: ferromagnetism, antiferromagnetism, the spin-crossover effect, and fluctuations in magnetic nanodiscs - Blundell, S; Pratt, F; Lancaster, T; Marshall, I; Steer, C; Hayes, W; Sugano, T; Letard, J; Caneschi, A; Gatteschi, D; Heath, S (2003)
We present the results of recent muSR experiments on a variety of novel organic and molecular magnetic systems. Muons are sensitive to local static fields and magnetic fluctuations, but can probe much more than just the onset of long-range magnetic order. We review our work on nitronyl nitroxide organic ferromagnets and anti ferromagnets. We describe a muon study of the spin-crossover phenomenon which has been studied in Fe(PM-PEA)(2)(NCS)(2), and which shows Gaussian and root-exponential muon relaxation in the high-spin and low-spin phases, respectively. Experiments on a disc-shaped molecular complex containing Fe-19 (with spin 31/2) reveal the effects of quantum tunneling of magnetization and allow an estimate of the quantum tunneling rate. (C) 2002 Elsevier Science B.V. All rights reserved.